Synthesis and supramolecular properties of regioisomers of mononaphthylallyl derivatives of γ-cyclodextrin - Bláhová, Markéta; Filippov, Sergey K.; Kováčik, Lubomír; Horský, Jiří; Hybelbauerová, Simona; Syrová, Zdenka; Křížek, Tomáš; Jindřich, Jindřich (Beilstein Journal of Organic Chemistry, 2017)
Monosubstituted derivatives of γ-cyclodextrin (γ-CD) are suitable building blocks for supramolecular polymers, and can also serve as precursors for the synthesis of other regioselectively monosubstituted γ-CD derivatives. We prepared a set of monosubstituted 2I-O-, 3I-O-, and 6I-O-(3-(naphthalen-2-yl)prop-2-en-1-yl) derivatives of γ-CD using two different methods. A key step of the first synthetic procedure is a cross-metathesis between previously described regioisomers of mono-O-allyl derivatives of γ-CD and 2-vinylnaphthalene which gives yields of about 16–25% (2–5% starting from γ-CD). To increase the overall yields, we have developed another method, based on a direct alkylation of γ-CD with 3-(naphthalen-2-yl)allyl chloride as the alkylating reagent. Highly regioselective reaction conditions, which differ for each regioisomer in a used base, gave the monosubstituted isomers in yields between 12–19%. Supramolecular properties of these derivatives were studied by DLS, ITC, NMR, and Cryo-TEM.
Keywords: γ-cyclodextrin; naphthylallyl derivatives; regioselective alkylation; supramolecular properties; synthesis

(untitled) - Crini, G. (Chem. Rev., 2014)

(untitled) - Řezanka, P.; Navrátilová, K.; Řezanka, M.; Král, V.; Sýkora, D. (Electrophoresis, 2014)

(untitled) - Xiao, Y.; Ng, S.-C.; Tan, T. T. Y.; Wang, Y. (J. Chromatogr. A, 2012)

(untitled) - Li, S.; Purdy, W. C. (Chem. Rev., 1992)

(untitled) - Szejtli, J. (J. Mater. Chem., 1997)

(untitled) - Harada, A.; Takashima, Y.; Yamaguchi, H. (Chem. Soc. Rev., 2009)

(untitled) - Miyauchi, M.; Kawaguchi, Y.; Harada, A. (J. Inclusion Phenom. Macrocyclic Chem., 2004)

(untitled) - Yuen, F.; Tam, K. C. (Soft Matter, 2010)

(untitled) - Brunsveld, L.; Folmer, B. J. B.; Meijer, E. W.; Sijbesma, R. P. (Chem. Rev., 2001)

(untitled) - Řezanka, M. (Eur. J. Org. Chem., 2016)

(untitled) - Řezanka, M.; Eignerová, B.; Jindřich, J.; Kotora, M. (Eur. J. Org. Chem., 2010)

(untitled) - Khan, A. R.; Forgo, P.; Stine, K. J.; D’Souza, V. T. (Chem. Rev., 1998)

(untitled) - Rong, D.; D’Souza, V. T. (Tetrahedron Lett., 1990)

(untitled) - Bláhová, M.; Bednářová, E.; Řezanka, M.; Jindřich, J. (J. Org. Chem., 2013)

(untitled) - Zhu, X.; Quaranta, A.; Bensasson, R. V.; Sollogoub, M.; Zhang, Y. (Chem. – Eur. J., 2017)

(untitled) - Inoue, Y.; Hakushi, T.; Liu, Y.; Tong, L.; Shen, B.; Jin, D. (J. Am. Chem. Soc., 1993)

(untitled) - Harada, A.; Takashima, Y.; Nakahata, M. (Acc. Chem. Res., 2014)

(untitled) - Puskás, I.; Schrott, M.; Malanga, M.; Szente, L. (J. Inclusion Phenom. Macrocyclic Chem., 2012)

(untitled) - Coleman, A. W.; Nicolis, I.; Keller, N.; Dalbiez, J. P. (J. Inclusion Phenom. Mol. Recognit. Chem., 1992)

(untitled) - Benkovics, G.; Hodek, O.; Havlikova, M.; Bosakova, Z.; Coufal, P.; Malanga, M.; Fenyvesi, E.; Darcsi, A.; Beni, S.; Jindrich, J. (Beilstein J. Org. Chem., 2016)

(untitled) - González-Gaitano, G.; Rodríguez, P.; Isasi, J. R.; Fuentes, M.; Tardajos, G.; Sánchez, M. (J. Inclusion Phenom. Macrocyclic Chem., 2002)

(untitled) - Bonini, M.; Rossi, S.; Karlsson, G.; Almgren, M.; Lo Nostro, P.; Baglioni, P. (Langmuir, 2006)

(untitled) - Peroche, S.; Parrot-Lopez, H. (Tetrahedron Lett., 2003)

(untitled) - Gèze, A.; Aous, S.; Baussanne, I.; Putaux, J.; Defaye, J.; Wouessidjewe, D. (Int. J. Pharm., 2002)

(untitled) - Šnajdr, I.; Janoušek, Z.; Jindřich, J.; Kotora, M. (Beilstein J. Org. Chem., 2010)

(untitled) - Tanaka, S.; Saburi, H.; Hirakawa, T.; Seki, T.; Kitamura, M. (Chem. Lett., 2009)

(untitled) - Tanaka, S.; Hirakawa, T.; Oishi, K.; Hayakawa, Y.; Kitamura, M. (Tetrahedron Lett., 2007)

(untitled) - Bouziane, A.; Hélou, M.; Carboni, B.; Carreaux, F.; Demerseman, B.; Bruneau, C.; Renaud, J.-L. (Chem. – Eur. J., 2008)

(untitled) - Tojima, T.; Katsura, H.; Nishiki, M.; Nishi, N.; Tokura, S.; Sakairi, N. (Carbohydr. Polym., 1999)

(untitled) - Řezanka, M.; Jindřich, J. (Carbohydr. Res., 2011)

(untitled) - Hanessian, S.; Benalil, A.; Laferriere, C. (J. Org. Chem., 1995)

(untitled) - Masurier, N.; Lafont, O.; Le Provost, R.; Lesur, D.; Masson, P.; Djedaini-Pilard, F.; Estour, F. (Chem. Commun., 2009)

(untitled) - Jindrich, J.; Pitha, J.; Bengt, L. (Carbohydr. Res., 1995)

(untitled) - Wenz, G.; Höfler, T. (Carbohydr. Res., 1999)

(untitled) - Jindřich, T.; Tišlerová, I. (J. Org. Chem., 2005)

(untitled) - Bertaut, E.; Landy, D. (Beilstein J. Org. Chem., 2014)

(untitled) - Lovatt, M.; Cooper, A.; Camilleri, P. (Eur. Biophys. J., 1996)

(untitled) - Heerklotz, H. H.; Binder, H.; Epand, R. M. (Biophys. J., 1999)

(untitled) - Illapakurthy, A. C.; Wyandt, C. M.; Stodghill, S. P. (Eur. J. Pharm. Biopharm., 2005)

Introduction to Macromolecular Science - Munk, P.; Aminabhavi, T. M. (Wiley-Interscience, 2002)

Magnetic Resonance Spectroscopy - Pessine, F. B. T.; Calderini, A.; Alexandrino, G. L. (InTechOpen, 2012)

(untitled) - Rekharsky, M. V.; Inoue, Y. (Chem. Rev., 1998)

(untitled) - Sau, S.; Solanki, B.; Orprecio, R.; Stam, J. V.; Evans, C. H. (J. Inclusion Phenom. Macrocyclic Chem., 2004)